Initiating Reversible Aqueous Copper–Tellurium Conversion Reaction with High Volumetric Capacity through Electrolyte Engineering. Issue 9 (2nd January 2023) - Sun, Yuanhe; Zhao, Yuanxin; Lei, Qi; Du, Wei; Yao, Zeying; Zhang, Wei; Si, Jingying; Ren, Zhiguo; Chen, Jige; Gao, Yi; Wen, Wen; Tai, Renzhong; et al.
Abstract: Pursuing conversion‐type cathodes with high volumetric capacity that can be used in aqueous environments remains rewarding and challenging. Tellurium (Te) is a promising alternative electrode due to its intrinsic attractive electronic conductivity and high theoretical volumetric capacity yet still to be explored. Herein, the kinetically/thermodynamically co‐dominat copper–tellurium (Cu–Te) alloying phase‐conversion process and corresponding oxidation failure mechanism of tellurium are investigated using in situ synchrotron X‐ray diffraction and comprehensive ex situ characterization techniques. By virtue of the fundamental insights into the tellurium electrode, facile and precise electrolyte engineering (solvated structure modulation or reductive antioxidant addition) is implemented to essentially tackle the dramatic capacity loss in tellurium, affording reversible aqueous Cu–Te conversion reaction with an unprecedented ultrahigh volumetric capacity of up to 3927 mAh cm −3, a flat long discharge plateau (capacity proportion of ≈81%), and an extraordinary level of capacity retention of 80.4% over 2000 cycles at 20 A g −1 of which lifespan thousand‐fold longer than Cu–Te conversion using CuSO4 –H2 O electrolyte. This work paves a significant avenue for expanding high‐performance conversion‐type cathodes toward energetic aqueous multivalent‐ion batteries. Abstract : The copper–tellurium conversion reaction with high volumetric capacity of 3927 mAh cm −3 and long discharge plateau are investigated. The thermodynamic–kinetic asymmetries of the Cu–Te multiphase‐conversion and oxidation‐failure mechanisms are systematically revealed. The developed precise electrolyte engineering overcomes inherent oxidative distress and extends the cycling life of the battery by about three orders of magnitude.